DEVELOPMENT OF PERSONALITY COMPETENCE OF PRESERVICE TEACHER AT DISRUPTION ERA - Siti Zumrotul Maulida; Ifah Silfianah; Ainun Nikmati Laily (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2018)
The disruption era is a challenge for the education sector because education is one of the areas that can support the quality of Indonesian human resources according to Kemenristekdikti priorities. This article aims to explore the development of personality competencies of preservice teachers in facing the challenges of disruption era. The function of teachers in the disruption era is different from that of teachers in the previous era, which is shifting to the function of cultivating ethical values, character, wisdom, experience, and social empathy because the function is impossible to do by machine. Thus, the challenge of educational institutions is to form the competence of preservice teacher personality which will build suitable exemplary based on expectation of teacher's role revolution in disruption era. There are four things that can be done in developing the personality competence of preservice teachers, some of them are: 1). religious matriculation programs, 2). application of student code of conduct, 3) Real Work Experience (KKN) program, and 4). integration of religious values in lectures.